Correlations between modest weight loss and leptin to adiponectin ratio, insulin and leptin resensitization in a small cohort of Norwegian individuals with obesity - Isaksen, Victoria Therese; Larsen, Maria; Goll, Rasmus; Paulssen, Eyvind Jakob; Florholmen, Jon (Endocrine and Metabolic Science, 2023)
Background - Weight loss is important to reduce the risk of metabolic complications in obese individuals, in whom dysregulated adipokines play a central role. This study aims to investigate whether dysregulated adipokines and postprandial triglycerides (TG) improve with a modest weight loss. Methods - Individuals with obesity (BMI ≥ 30 kg/m2) were recruited among patients at the University Hospital of North Norway and the Stamina Health weight loss rehabilitation program. We measured resting energy expenditure (REE), and calculated the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), leptin to adiponectin (L:A) ratio, indirect leptin sensitivity (REE:leptin ratio), postprandial TG clearance at 6 h, and TG response before and after weight loss. The goal of the weight loss intervention was a loss of ≥5 % of initial total body weight. Results - 28 participants completed the study, of which 13 lost ≥ 5 % body weight and 18 lost <5 % body weight. HOMA-IR (−23.1 %), REE:leptin ratio (+80.1 %) and L:A ratio (−45.7 %) significantly improved with weight loss, whereas there was no improvement of postprandial TG response or clearance. No significant changes were observed in the non-weight loss group. Conclusion - The data are consistent with the general concept that modest weight loss in obese patients may restore metabolic regulation by improving L:A ratio and insulin and leptin sensitivity.